THE DESCRIPTION OF CHARACTER EDUCATION ON SCIENTIFIC APPROACH IN ENGLISH LEARNING TO THE STUDENTS OF SMP NEGERI 1 KERAMBITAN - Gusti Ayu Gede Sukraningsih; Galuh Kusuma Wardani (FAKULTAS PENDIDIKAN BAHASA DAN SENI IKIP SARASWATI, 2021)
The purpose of national education contains human values utilized as the source in the development of character education which is developed at every level of education. This research is aimed at describing character education in English learning to the students of SMP Negeri 1 Kerambitan. This research used descriptive qualitative research method. The data were collected by utilizing the techniques of observation, interview, and documentation. The data analysis were conducted with qualitative data analysis including data reduction, data display, conclusion, and verification. The result of this research showed that: (1) Character education was implemented in learning process in the phases of observing, questioning, collecting data, associating, and communicating (2). The values of character appeared in scientific approach were developing diligence, discipline, coriousity, creativity, having good reading habit, independence, responsibility, and communication. In the implementation, some students were still not able to run the character values well. The conclusion of this research is character education on scientific approach in English learning is implemented quite well considering that some students were still not able to adjust the values of charcter well. Therefore, it is recommended that the learning activities need to be carried out more interactively, inspiring, challenging, and motivating learners to be actively participated in learning process.